2023
DOI: 10.1007/s11356-023-25588-3
|View full text |Cite
|
Sign up to set email alerts
|

Continuum from microplastics to nanoplastics: effects of size and source on the estuarine bivalve Scrobicularia plana

Abstract: Plastic has been largely detected in estuarine environments and represent major concern towards aquatic living organisms. Whereas the majority of previous studies analyze the effects of standard particles, mainly polystyrene (PS), not representative to what is found in natural environments, the present study evaluates the impact of microplastics (MPs) and nanoplastics (NPs) under realistic exposure conditions. Scrobicularia plana individuals were exposed to low concentrations (0.008, 10 and 100 µg L − 1 ) of e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 99 publications
(76 reference statements)
2
5
0
Order By: Relevance
“…No alteration of the CI was demonstrated for the different plastic particles tested. Our results agree with previous studies that have shown no effect of plastic particles on the body condition index of different bivalves (Bour et al, 2018;Joyce and Falkenberg, 2022;Métais et al, 2023;Ribeiro et al, 2017;Von Moos et al, 2012).…”
Section: Condition Indexsupporting
confidence: 93%
See 2 more Smart Citations
“…No alteration of the CI was demonstrated for the different plastic particles tested. Our results agree with previous studies that have shown no effect of plastic particles on the body condition index of different bivalves (Bour et al, 2018;Joyce and Falkenberg, 2022;Métais et al, 2023;Ribeiro et al, 2017;Von Moos et al, 2012).…”
Section: Condition Indexsupporting
confidence: 93%
“…In their study, these authors also reported higher growth inhibition of microalgae S. subspicatus exposed to environmental NPs than standard ones (Baudrimont et al, 2019). In addition, two studies using the same plastic particles as in our study demonstrated that PS NPs did not present the same toxicity as compared to ENV MPs and NPs in the mussel Mytilus edulis and clam Scrobicularia plana (Métais et al, 2023;Roman et al, 2023). However, there is a knowledge gap on the mechanisms of toxicity of environmental MPs and NPs, and further investigations are needed to explore their potential joint toxicity with chemicals.…”
Section: Journal Pre-proofsupporting
confidence: 65%
See 1 more Smart Citation
“…The selection of PS-NPs exposure concentrations was informed by the NPs concentration in their natural habitat and toxicological research findings from other research. 4,23 A seven-day toxicological experiment was conducted under semistatic conditions to assess the effects of the exposure solution on the test subjects. Fluorescence intensity measurements were obtained each time the exposure solution was prepared and replaced to ensure the accurate concentration of the exposure solution throughout the study.…”
Section: Chemicals and Domestication Of M Hongkongensismentioning
confidence: 99%
“…3 Exposure to NPs at concentrations of 10 μg/L and 100 μg/L was observed to alter the catalytic activities of catalase (CAT) and glutathione s-transferase (GST) within the gill and gonad tissues in Scrobicularia plana. 4 Besides, when exposed to 100 mg/L NPs, a large number of oyster sperm and eggs became deformed. 5 The intestine serves as the primary organ for nutrient absorption and digestion in oysters, and it is the initial site for the entry and accumulation of toxins.…”
Section: Introductionmentioning
confidence: 99%